Narrative and Bodily Identity in Eating Disorders: Toward an Integrated Theoretical-Clinical Approach - Pellegrini, Rosa Antonella; Finzi, Sarah; Veglia, Fabio; Di Fini, Giulia (Frontiers in Psychology, 2021)
Eating disorders (EDs) can be viewed as "embodied acts" that help to cope with internal and external demands that are perceived as overwhelming. The maintenance of EDs affects the entire identity of the person; the lack of a defined or valid sense of self is expressed in terms of both physical body and personal identity. According to attachment theory, primary relationships characterized by insecurity, traumatic experiences, poor mirroring, and emotional attunement lead to the development of dysfunctional regulatory strategies. Although the literature shows an association between attachment style or states of mind, trauma, behavioral strategies, and various EDs, the debate is still ongoing and the results are still conflicting. Therefore, we believe it is important to examine and treat EDs by understanding which narrative trajectory intercepts distress in relation to narrative and embodied self-concept. Drawing on clinical observation and a narrative review of the literature, we focus on the construction and organization of bodily and narrative identity. Because bodily representations are the primary tools for generating meaning, organizing experience, and shaping social identity from the earliest stages of life, we focus on the role that bodily interactions and sensorimotor and proprioceptive patterns have played in the development of EDs. We consider the role that lack of attunement, insecure attachment, and relational trauma play in mentalizing, affecting self-representation and emotion regulation strategies. The paper also considers a semantic mode of trauma in EDs that involves a top-down pathway through beliefs and narratives about oneself based on lack of amiability, on devaluation, and on humiliation memories. Finally, we would like to highlight the proposal of an integrated model with multiple access model to psychotherapy that takes into account the complexity of ED patients in whom aspects related to dysregulation, body image disintegration, and posttraumatic symptoms are associated with a suffering sense of self and a retraumatizing narrative.